1986
DOI: 10.1002/cber.19861191218
|View full text |Cite
|
Sign up to set email alerts
|

Wasserstoffübertragungen, 10. Der cis‐selektive, zweistufige Wasserstoff‐Transfer von 1,4‐Dihydroarenen auf o‐ und p‐Chinone

Abstract: Der Wasserstoff-Transfer von den 1,4-Dihydroarenen 1 und 2 lauft nicht als -hier symmetrieerlaubte -Synchronreaktion ab, obwohl Deuterium-Markierung eine 2.T. sehr hohe cis-Selektivitat der Abstraktion beweisen. Losungsmitteleffekte wie Einzel-lsotopeneffekte entsprechen vielmehr einer primaren Hydrid-ubertragung. Die sterische Fixierung im Ionenpaar steigt beim grokren n-System von 2, sie sinkt bei polaren Losungsmitteln. Die Hohe der primaren Isotopeneffekte entspricht einem deutlichen Anteil des Tunnel-Effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Related orders of hydride abstraction rates from the dihydroarenes 3 , 4 , and 5 (Tables and ) have also been found in their reactions with other hydride acceptors (Table ). It should be noted, however, that for the reactions of dihydroarenes with quinones the possibility of concerted didehydrogenation with direct formation of arenes has been discussed. , …”
Section: Discussionmentioning
confidence: 99%
“…Related orders of hydride abstraction rates from the dihydroarenes 3 , 4 , and 5 (Tables and ) have also been found in their reactions with other hydride acceptors (Table ). It should be noted, however, that for the reactions of dihydroarenes with quinones the possibility of concerted didehydrogenation with direct formation of arenes has been discussed. , …”
Section: Discussionmentioning
confidence: 99%
“…Independent support for this conclusion comes from an investigation of the kinetic isotope effect observed in the DDQ oxidation of the tetralin derivatives 9/9-1,1,4,4-D 4 and 9-D 12 . Heesing et al [34] have carefully studied the stereochemical course and the kinetic isotope effects for the oxidation of 1,2-dihydronaphthalene (7) and 1,3-cyclohexadiene (28) with the deuterated derivatives shown in Scheme 5 and various quinones such as 1 a and 10. The oxidation of cis-and trans-7-1,2-D 2 and À28-5,6-D 2 proceeds with 90 % and 98 % cis stereoselectivity, respectively.…”
mentioning
confidence: 99%
“…Several mechanistic pathways for the oxidation of benzylic C-H bonds with DDQ have been proposed, and these mechanisms have been investigated by a number of groups. [42][43][44][45][46][47][48][49] Detailed studies by Linstead, Jackman, and co-workers [50][51][52][53] concluded that most DDQ oxidations occur through a ratedetermining hydride transfer, leading to a delocalized carbocation which rapidly loses a proton or is trapped by a nucleophile. This mechanism is supported by ab initio calculations on the oxidation of cyclohexa-1,4-diene with DDQ that predicts an ionic mechanism in which an initial hydride transfer occurs.…”
Section: Resultsmentioning
confidence: 99%